Comparative analysis of the gut bacteria and fungi in migratory demoiselle cranes (Grus virgo) and common cranes (Grus grus) in the Yellow River Wetland, China - Li, Ziteng; Duan, Tianfeng; Wang, Lin; Wu, Jiawei; Meng, Yajie; Bao, Dulan; Gao, Li; Liu, Li (Frontiers in Microbiology, 2024)
Gut microbiota are closely related to the nutrition, immunity, and metabolism of the host and play important roles in maintaining the normal physiological activities of animals. Cranes are important protected avian species in China, and they are sensitive to changes in the ecological environment and are thus good environmental indicators. There have been no reports examining gut fungi or the correlation between bacteria and fungi in wild Demoiselle cranes (Grus virgo) and Common cranes (Grus grus). Here, 16S rRNA and ITS high-throughput sequencing techniques were used to analyze the gut bacterial and fungal diversity of Common and Demoiselle cranes migrating to the Yellow River wetland in Inner Mongolia, thus providing a foundation for the protection of rare wild animals.The results revealed that for gut bacteria α diversity, Chao1 index in Demoiselle cranes was remarkably higher than that in Common cranes (411.07±79.54 vs. 294.92±22.38), while other index had no remarkably differences. There was no remarkable difference in fungal diversity. There were marked differences in the gut microbial composition between the two crane species. At the phylum level, the highest abundance of bacteria in the Common crane and Demoiselle crane samples was Firmicutes, accounting for 87.84% and 74.29%, respectively. The highest abundance of fungi in the guts of the Common and Demoiselle cranes was Ascomycota, accounting for 69.42% and 57.63%, respectively. At the genus level, the most abundant bacterial genus in the Common crane sample was Turicibacter (38.60%), and the most abundant bacterial genus in the Demoiselle crane sample was Catelicoccus (39.18%). The most abundant fungi in the Common crane sample was Penicillium (6.97%), and the most abundant fungi in the Demoiselle crane sample was Saccharomyces (8.59%).Correlation analysis indicated that there was a significant correlation between gut bacteria and fungi.This study provided a research basis for the protection of cranes. Indeed, a better understanding of the gut microbiota is very important for the conservation and management of wild birds, as it not only helps us to understand their life history and related mechanisms, but also can hinder the spread of pathogenic microorganisms.